Repeated exposure to kairomone-containing coffee odor improves abnormal olfactory behaviors in heterozygous oxytocin receptor knock-in mice - Osada, Kazumi; Kujirai, Riyuki; Hosono, Akira; Tsuda, Masato; Ohata, Motoko; Ohta, Tohru; Nishimori, Katsuhiko (Frontiers in Behavioral Neuroscience, 2023)
The oxytocin receptor (OXTR) knock-out mouse is a model of autism spectrum disorder, characterized by abnormalities in social and olfactory behaviors, and learning. Previously, we demonstrated that OXTR plays a crucial role in regulating aversive olfactory behavior to butyric acid odor. In this study, we attempted to determine whether coffee aroma affects the abnormal olfactory behavior of OXTR-Venus knock-in heterozygous mice [heterozygous OXTR (+/−) mice] using a set of behavioral and molecular experiments. Four-week repeated exposures of heterozygous OXTR (+/−) mice to coffee odor, containing three kairomone alkylpyrazines, rescued the abnormal olfactory behaviors compared to nonexposed wild-type or heterozygous OXTR (+/−) mice. Increased Oxtr mRNA expression in the olfactory bulb and amygdala coincided with the rescue of abnormal olfactory behaviors. In addition, despite containing the kairomone compounds, both the wild-type and heterozygous OXTR (+/−) mice exhibited a preference to the coffee odor and exhibited no stress-like increase in corticotropin-releasing hormone, instead of a kairomone-associated avoidance response. The repeated exposures to the coffee odor did not change oxytocin and estrogen synthetase/receptors as a regulator of the gonadotropic hormone. These data suggest that the rescue of abnormal olfactory behaviors in heterozygous OXTR (+/−) mice is due to the coffee odor exposure-induced OXTR expression.